Labour or capital factors: Which influence industrial automation more? - Marcin Gryczka (International Entrepreneurship Review)
Objective: The purpose of the article is to determine which economic factors, specifically those related to labour and capital, have a more significant impact on the level of industrial automation. This assessment is based on robot density per 10 000 employees in the manufacturing sector.